2006
DOI: 10.1063/1.2198828
|View full text |Cite
|
Sign up to set email alerts
|

An experimental value for the B1u C–H stretch mode in benzene

Abstract: We here present experimental infrared spectra on two (C6H6)(C6D6) benzene dimer isomers in the gas phase. The spectra show that the two benzene molecules in the dimer are symmetrically inequivalent and have distinct IR signatures. One of the two molecules is in a site of low symmetry, which leads to the IR activation of fundamental modes that are IR forbidden by symmetry in the monomer. In the spectra, all four fundamental C–H stretch modes of benzene are observed. Modes in the dimer are shifted up to 3cm−1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 25 publications
10
86
1
Order By: Relevance
“…30,[32][33][34][35]38,41,42 When it was discovered 38,42,49 that the T-shape structure is further stabilized by a slight tilt of the monomers, it became clear that the (tilted) T-shaped structure is lower in energy than the parallel-displaced structure. The experimental evidence 17,[19][20][21][22][23] confirms this conclusion. Although the energy difference between the two structures is small, the parallel-displaced structure is not observed in experiments due to collisions with the carrier gases used.…”
Section: Introductionmentioning
confidence: 54%
“…30,[32][33][34][35]38,41,42 When it was discovered 38,42,49 that the T-shape structure is further stabilized by a slight tilt of the monomers, it became clear that the (tilted) T-shaped structure is lower in energy than the parallel-displaced structure. The experimental evidence 17,[19][20][21][22][23] confirms this conclusion. Although the energy difference between the two structures is small, the parallel-displaced structure is not observed in experiments due to collisions with the carrier gases used.…”
Section: Introductionmentioning
confidence: 54%
“…These results, too, are in agreement with the experimentally observed red-shift of 3 cm −1 for these modes and also theoretical calculations of the vibrational spectra for the T-shape structure. [36][37][38] FIG. 2.…”
mentioning
confidence: 99%
“…26 In the last year, Ramón and Grańa 27 have reported "blue shifting"hydrogen bond for the classical T-shaped configurations of the benzene dimer and benzene-naphthalene complexes using MP2 / 6-31+ + G ‫ءء‬ level. In contrast, a recent experimental study by Erlekam et al 24 revealed that the IR active modes of the C-H stretching vibrations of the benzene dimer are shifted up to 3 cm −1 to the "red" compared to the monomer. This experimental result raises challenging questions to theoreticians: ͑a͒ Does MP2 method fail to predict the red shift of vibrational frequency?…”
Section: Department Of Chemistry Interdisciplinary Center Formentioning
confidence: 50%
“…Erlekam et al 24,25 assigned T-shaped configuration for the benzene dimer based on their IR spectra. Therefore, we have considered different T-shaped configurations of the benzene dimer in this work in order to probe the reliability of theoretical approaches ͑Fig.…”
Section: Department Of Chemistry Interdisciplinary Center Formentioning
confidence: 99%
See 1 more Smart Citation